Software courses in interactive Malaysia map for children (IMMFC) - Nur Hashibah, Rozi (2015)
Learning material made by a teacher in the classroom sometimes have problems because of the lack of learning materials attract the attention of students. By developing systems directly to student learning can reduce the burden on teachers in preparing teaching materials and enables information to be received without taking a long time. In discussing the project this time Sofware Courses in Interactive Malaysia Map For Children (IMMFC) where it is illustration approach that has been to facilitate the process of learning map. The project consist of interactive page designed to hlp students to visualize their understanding in Kajian Tempatan subject. During the development IMMFC, methodology used is based on (Analysis, Design, Development, Implement and Evaluate) ADDIE. Each poses in the development process followed by each phase in the ADDIE.